Proposed Business Strategy Improvement In The New Normal - Saskia Elsya Ayudhia; Andika Putra Pratama (Syntax Corporation, 2022)
The impact of the COVID-19 outbreak on the socio-economic sector is predicted to increase Indonesia's average poverty rate by the end of 2020. This pandemic outbreak also has an impact on the economic sector, including to White Grass. White Grass is an online store that focuses on selling handmade and crafted goods for home decoration. This rtudy aimed to thoroughly understand the underlying reason cause White Grass sales is very volatile and find insights of the right business strategy for White Grass in the New Normal. This study was quantitative and qualitative method. The data was collected by primary and secondary data through interview and questionnaire. The data was analysed by internal, external, and SWOT analysis. To promote their products, White Grass had some innovations. White Grass changed the name of its product variations to make it easier to remember and give the impression of a signature of White Grass even though the product is an imported product. White Grass currently has two online distribution channel through its Shopee Official Account & TikTok Shop. The promotion conducted by White Grass is through the social media sponsorship and endorsement to selected influencer. White Grass also apply special offer or bundles program during during pay day week where people got their salary and launch the product unique twin-date like 8.8, 9.9, 10.10.